PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELI PADA ANGKRINGAN MAS JUNS DI KOTA SAMARINDA - Elfreda A Lau, Tyas Riris Nurdiansyah, LCA. Robin Jonat (EKONOMIA, 2015)
Angkringan effort in Samarinda growing rapidly angkringan marked with the number of new businesses established. One of them is Angkringan Mas Juns that have good potential for the development of business with consumers more and more. Many of today's consumer, make not all consumers can obtain maximum service. So that business owners plan to rent a place of business bigger with the addition of facilities for services provided can be maximized.The purpose of this study was to determine whether the factor of discounting and promotion of social media affect the sale in Angkringan Mas Juns. Formulation of the problem in this study is whether the promotion activities significantly influence the increase in the sales of the product on Angkringan Mas Juns in Samarinda. 50 respondents participated in the study. Data collection method is by using a questionnaire and analyzed using multiple linear regression analysis.Results of the analysis showed that the granting of discounts and promotional social media influence on sales results in Angkringan Mas Juns well together or partially.